The SmartAG partner: CCAFS East Africa Bi-annual Newsletter, January - June 2017 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
We are pleased to share with you our SmartAg Partner newsletter, highlighting policy engagement and ongoing research from January to June 2017.